INTEGRATED NUTRIENT MANAGEMENT IN BLACKGRAM-POTATO-WHEAT SEQUENCE IN MADHYA PRADESH - Singh, S. P.; Kushwah, V. S.; Lal, S. S. (Potato Journal, 2013)
A field experiment was conducted in RBD during 2004-05 at Gwalior to study the effect of organic manures and inorganic fertilizers on ware potato production in blackgram-potato-wheat sequence. Application of manures and fertilizers increased plant height and potato haulm and tuber yield significantly. The highest plant height (150 cm) was recorded with the treatment where 100% recommended dose of NPK was applied through fertilizers. It was statistically on par with the treatments where Nadep compost/FYM were applied with 50% recommended dose of NPK. Highest tuber yield was recorded with 100% NPK applied treatment. Tuber yield in other treatments was statistically at par. Incremental benefit cost ratio was highest with the treatment where only Nadep compost was applied. Though highest tuber yield was recorded with the 100% recommended NPK applied treatment but this treatment recorded lowest incremental benefit cost ratio on account of increased additional cost.